Decoding IEEE 802.11a/g/p OFDM in software using GNU radio - Bloessl, Bastian; Segata, Michele; Sommer, Christoph; Dressler, Falko (Proceedings of the 19th annual international conference on Mobile computing & networking - MobiCom '13)

An IEEE 802.11a/g/p OFDM receiver for GNU radio - Bloessl, Bastian; Segata, Michele; Sommer, Christoph; Dressler, Falko (Proceedings of the second workshop on Software radio implementation forum - SRIF '13)

To crash or not to crash: Estimating its likelihood and potentials of beacon-based IVC systems - Joerer, Stefan; Segata, Michele; Bloessl, Bastian; Cigno, Renato Lo; Sommer, Christoph; Dressler, Falko (2012 IEEE Vehicular Networking Conference (VNC))

A Vehicular Networking Perspective on Estimating Vehicle Collision Probability at Intersections - Joerer, Stefan; Segata, Michele; Bloessl, Bastian; Lo Cigno, Renato; Sommer, Christoph; Dressler, Falko (IEEE Transactions on Vehicular Technology)

Use both lanes: Multi-channel beaconing for message dissemination in vehicular networks - Klingler, Florian; Dressler, Falko; Cao, Jiannong; Sommer, Christoph (2013 10th Annual Conference on Wireless On-demand Network Systems and Services (WONS))

Fair and adaptive data dissemination for Traffic Information Systems - Schwartz, Ramon S.; Ohazulike, Anthony E.; Sommer, Christoph; Scholten, Hans; Dressler, Falko; Havinga, Paul (2012 IEEE Vehicular Networking Conference (VNC))

On the applicability of fair and adaptive data dissemination in traffic information systems - Schwartz, Ramon S.; Ohazulike, Anthony E.; Sommer, Christoph; Scholten, Hans; Dressler, Falko; Havinga, Paul (Ad Hoc Networks)

On the applicability of Two-Ray path loss models for vehicular network simulation - Sommer, Christoph; Joerer, Stefan; Dressler, Falko (2012 IEEE Vehicular Networking Conference (VNC))

How shadowing hurts vehicular communications and how dynamic beaconing can help - Sommer, Christoph; Joerer, Stefan; Segata, Michele; Tonguz, Ozan; Cigno, Renato Lo; Dressler, Falko (2013 Proceedings IEEE INFOCOM)

IVC in Cities: Signal Attenuation by Buildings and How Parked Cars Can Improve the Situation - Sommer, Christoph; Eckhoff, David; Dressler, Falko (IEEE Transactions on Mobile Computing)

Analyzing and Quantifying Fault Tolerance Properties - Hellebrand, Sybille (14th IEEE Latin American Test Workshop - (LATW'13))

Helping High Schoolers Move the (Virtual) World - Domik, Gitta; Arens, Stephan; Stilow, Peter; Friedrich, Hauke (IEEE computer graphics and applications)

The use of code reading in teaching programming - Busjahn, Teresa; Schulte, Carsten (Koli Calling)

Object Interaction Competence Model v. 2.0 - Bennedsen, Jens; Schulte, Carsten (LaTiCE)

PCK and reflection in computer science teacher education - Buchholz, Malte; Saeli, Mara; Schulte, Carsten (WiPSCE)

Reflections on the role of programming in primary and secondary computing education - Schulte, Carsten (WiPSCE)

Labelwise versus pairwise decomposition in label ranking - Cheng, W.; Henzgen, S.; Hüllermeier, Eyke (In Proceedings Workshop LWA-2009, Lernen-Wissensentdeckung-Adaptivität, Bamberg, Germany)

Rectifying classifier chains for multi-label classification, Bamberg, Germany - Senge, Robin; del Coz, J.; Hüllermeier, Eyke (In Proceedings Workshop LWA-2009, Lernen-Wissensentdeckung-Adaptivität, Bamberg, Germany)

Preference-based evolutionary optimization using generalized racing algorithms - Busa-Fekete, Robert; Fober, T.; Hüllermeier, Eyke (in Proceedings 23th Workshop Computational Intelligence, Dortmund Germany)

Weighted rank correlation measures based on fuzzy order relations - Henzgen, S.; Hüllermeier, Eyke (in Proceedings 23th Workshop Computational Intelligence, Dortmund Germany)

Interactive Q-learning with ordinal rewards and unreliable tutor - Weng, P.; Busa-Fekete, Robert; Hüllermeier, Eyke (In Proceedings ECML/PKDD-Workshop on Reinforcement learning from Generalized Feedback:Beyond Numerical Rewards, Prague)

Preference-based evolutionary direct policy search - Busa-Fekete, Robert; Szörenyi, B.; Weng, P.; Hüllermeier, Eyke (In Proceedings ECML/PKDD-Workshop on Reinforcement learning from Generalized Feedback:Beyond Numerical Rewards, Prague)

A nearest neigbor approach to label ranking based on generalized labelwise loss minimization - Cheng, W.; Hüllermeier, Eyke (In Proceedings M-PREF`13, 7th Multidisciplinary Workshop on Advances in Preference Handling Beijing, China)

Event history analysis on data streams: An application to earthquake occurence - Shaker, Ammar; Hüllermeier, Eyke (In Proceedings RealStream 2013, 1st International Workshop on Real-World Challenges for Data Stream Mining, Prague, Czech Republic)

On the problem of error propagation in classier chains for multi-label classification. Data Analysis, Machine Learning and Knowledge Discovery - Senge, Robin; del Coz, J.J.; Hüllermeier, Eyke (In Proceedings of GFKL-2012, 36th Annual Conference of the German Classification Society, Studies in Classification, Data Analysis and Knowledge Organization, Hildesheim, Germany)

Local clique merging: An extension of the maximum common subgraph measure with applications in structural bioinformatics, Algorithms from and for Nature and Life - Fober, T.; Klebe, G.; Hüllermeier, Eyke (In Proceedings GFKL-2011, Conference of the German Classification Society, Frankfurt Germany)

Formation and control of Turing patterns in a coherent quantum fluid - Ardizzone, Vincenzo; Lewandowski, Przemyslaw; Luk, M. H.; Tse, Y. C.; Kwong, N. H.; Lücke, Andreas; Abbarchi, Marco; Baudin, Emmanuel; Galopin, Elisabeth; Bloch, Jacqueline; Lemaitre, Aristide; Leung, P. T.; et al. (Scientific Reports)

Charge Photogeneration in Donor–Acceptor Conjugated Materials: Influence of Excess Excitation Energy and Chain Length - Tautz, Raphael; Da Como, Enrico; Wiebeler, Christian; Soavi, Giancarlo; Dumsch, Ines; Fröhlich, Nils; Grancini, Giulia; Allard, Sybille; Scherf, Ullrich; Cerullo, Giulio; Schumacher, Stefan; Feldmann, Jochen (Journal of the American Chemical Society)

Transverse optical instability patterns in semiconductor microcavities: Polariton scattering and low-intensity all-optical switching - Luk, M. H.; Tse, Y. C.; Kwong, N. H.; Leung, P. T.; Lewandowski, Przemyslaw; Binder, R.; Schumacher, Stefan (Physical Review B)

Excited-State Absorption of Conjugated Polymers in the Near-Infrared and Visible: A Computational Study of Oligofluorenes - Ling, Sanliang; Schumacher, Stefan; Galbraith, Ian; Paterson, Martin J. (The Journal of Physical Chemistry C)

On the insecurity of XML Security - Somorovsky, Juraj
XML Encryption and XML Signature describe how to apply encryption and signing algorithms to XML documents. These specifications are implemented in a wide range of systems and frameworks processing sensitive data, including banking, eGovernment, eCommerce, military, and eHealth infrastructures. The article presents practical and highly critical attacks which allow to forge signed XML documents or reveal contents of encrypted XML data.

A New Approach towards DoS Penetration Testing on Web Services - Falkenberg, Andreas; Mainka, Christian; Somorovsky, Juraj; Schwenk, Jörg (2013 IEEE 20th International Conference on Web Services)

Penetration test tool for XML-based web services - Mainka, Christian; Mladenov, Vladislav; Somorovsky, Juraj; Schwenk, Jörg (CEUR Workshop Proceedings)

One Bad Apple: Backwards Compatibility Attacks on State-of-the-Art Cryptography - Jager, Tibor; Paterson, Kenneth G.; Somorovsky, Juraj (20th Annual Network and Distributed System Security Symposium, NDSS 2013, San Diego, California, USA, February 24-27, 2013)

Der Einfluss von Steuern auf Investitionsentscheidungen bei Unsicherheit - Sureth, Caren

Fast Multi-update Operations on Compressed XML Data - Böttcher, Stefan; Hartel, Rita; Jacobs, Thomas (Big Data - 29th British National Conference on Databases, BNCOD 2013,)

DAG - Index - A Compressed Index for XML Keyword Search - Böttcher, Stefan; Brandenburg, Marc; Hartel, Rita (WEBIST 2013 - Proceedings of the 9th International Conference on Web Information Systems and Technologies)

Ordinal Choquistic regression - Fallah Tehrani, A.; Hüllermeier, Eyke (in Proceedings EUSFLAT-2013 8th International Conference on the European Society for Fuzzy Logic and Technology, Milano, Italy)

Fuzzy Pattern Trees as an alternative to rule-based fuzzy systems: Knowledge-driven, data-driven and hybrid modeling of colour yield in poyester dyeing, Edmonton, Canada - Nasiri, N.; Fober, T.; Senge, Robin; Hüllermeier, Eyke (in Proceedings IFSA-2013 World Congress of the International Fuzzy Systems Association, Edmonton, Canada)

Implementing Efficient Updates in Compressed Big Text Databases - Böttcher, Stefan; Bültmann, Alexander; Hartel, Rita; Schlüßler, Jonathan (International Conference on Database and Expert Systems Applications)

How visualization courses have changed over the past 10 years - Owen, G Scott; Domik, Gitta; Ebert, David S; Kohlhammer, J{\; Rushmeier, Holly; Santos, Beatriz Sousa; Weiskopf, Daniel (IEEE computer graphics and applications)

Animatronics Workshop: A Theater+ Engineering Collaboration at a High School - Alford, Jennifer Ginger; Jacob, Lucas; Dietz, Paul (IEEE computer graphics and applications)

Visualizing Dissections of the Heart in a Dataflow-based Shader Framework for Volume Rendering - Arens, Stephan; Bolte, Matthias; Domik, Gitta (Vision, Modeling & Visualization)

Highly Anisotropic Steel Processed by Selective Laser Melting - Niendorf, Thomas; Leuders, Stefan; Riemer, Andre; Richard, Hans Albert; Tröster, Thomas; Schwarze, Dieter (Metallurgical and Materials Transactions B)

Stahl-CFK-Strukturen wie Tiefziehteile fertigen - Schmidt, H. C.; Lauter, Christian (MaschinenMarkt Compositesworld)

Verhalten von lasergeschmolzenen Bauteilen aus der Titan-Aluminium-Legierung TiAl6V4 unter zyklischer Beanspruchung∗ - Riemer, Andre; Leuders, S.; Richard, Hans A.; Tröster, Thomas (Materials Testing)

Graded Lightweight Structures Through Hot Forming - Marten, Thorsten; Block, Holger; Tröster, Thomas; Gerber, Thomas; Sikora, Sascha; Lenze, Franz-Josef

Influences of Automotive Process Characteristics on Hybrid Structures - Lauter, Christian; Hochschulz, T.; Frantz, Meike; Tröster, Thomas

Curing of fibre reinforced plastics by resistance heating of sheet metal in a hybrid structure - Siewers, Bernd; Lauter, Christian; Tröster, Thomas

Crashworthiness of Hybrid Structures - Tröster, Thomas; Lauter, Christian; Reuter, C.